2018
DOI: 10.3390/ijms19071981
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Quantitative Proteomics Combined with Biological Validation Reveals Activation of Wnt/β-Catenin Pathway Contributing to Trastuzumab Resistance in Gastric Cancer

Abstract: Resistance to trastuzumab, which specifically target HER2-positive breast and gastric cancer, can develop ultimately in cancer patients. However, the underlying mechanisms of resistance in gastric cancer have not been fully elucidated. Here, we established trastuzumab-resistant MKN45 and NCI N87 gastric cancer sublines from their parental cells. The resistant cells exhibited characteristics of epithelial-mesenchymal transition (EMT) and acquired higher migratory and invasive capacities. To exploit the activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…EMT‐expressing cancer cells showed decreased expression of epithelial cell markers such as E‐cadherin and ZO‐1, while expression of mesenchymal cell markers such as vimentin and N‐cadherin increased. Although there is increasing evidence that EMT is closely related to the development of drug resistance in gastric cancer cells, its underlying mechanisms have not yet been fully elucidated …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT‐expressing cancer cells showed decreased expression of epithelial cell markers such as E‐cadherin and ZO‐1, while expression of mesenchymal cell markers such as vimentin and N‐cadherin increased. Although there is increasing evidence that EMT is closely related to the development of drug resistance in gastric cancer cells, its underlying mechanisms have not yet been fully elucidated …”
Section: Introductionmentioning
confidence: 99%
“…Although there is increasing evidence that EMT is closely related to the development of drug resistance in gastric cancer cells, its underlying mechanisms have not yet been fully elucidated. [14][15][16] To date, many studies have investigated the role of oestrogen receptor (ER) in gastric cancer, and the possible mechanisms of these effects and the clinical relevance of dysregulated ER in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Protein concentration was determined using a Bradford protein assay kit (P0006; Beyotime, China). Samples (200 g each) containing extracted membrane proteins were digested with trypsin, as described previously (54). Tryptic peptides were preseparated on a Waters 2695 HPLC system equipped with a C 18 column (5 m, 4.6 ϫ 250 mm; Thermo Fisher) and eluted using a continuous acetonitrile gradient as follows: time ϭ 0 min, 100% A (water), 0% B (acetonitrile), 0.5 ml/min; time ϭ 35 min, 2% A (water), 98% B (acetonitrile), 0.5 ml/min; and time ϭ 40 min, 2% A (water), 98% B (acetonitrile), 0.5 ml/ min.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot was performed according to standard protocols as described previously. 13,14 To put it briey, cells were collected and lysed with RIPA lysis buffer (50 mM Tris, 150 mM NaCl, 1% Triton X-100, 1% sodium deoxycholate, 0.1% SDS, Beyotime) containing 1% protease inhibitor. Then lysates were centrifuged at 12 000g for 15 min at 4 C, and the supernatants were collected for further use.…”
Section: Western Blotmentioning
confidence: 99%
“…8,12 Our previous proteomics demonstrated that acquired resistance to trastuzumab leads to distinct alterations of several signaling pathways in NCI N87/R and MKN45/R cells, out of which mTOR and Wnt/ b-catenin were conrmed by further studies. 13,14 Recently, we explored transcription factors related to trastuzumab resistance in NCI N87/R cells by liquid chromatography-mass spectrometry coupled with concatenated tandem array of transcription factor response elements (catTFRE) pull down proteomic technique. Our study indicated several transcription factors including TCF7L2, TCF7, FOXC1, JUN, MYC, FOS, ELK4, FOXC and DDIT3 had a crucial regulatory effect on epithelialmesenchymal transformation (EMT), Wnt/b-catenin and MAPK signaling pathways contributing to trastuzumab-resistance.…”
Section: Introductionmentioning
confidence: 99%